Association of TyG index with prehypertension or hypertension: a retrospective study in Japanese normoglycemia subjects - Xu, Jingtao; Xu, Weigan; Chen, Guojun; Hu, Qiaohua; Jiang, Jun (Frontiers in endocrinology (Lausanne), 2023)
The objective of our study was to investigate the potential association between the triglyceride and glucose (TyG) index and the occurrence of prehypertension or hypertension in a cohort of normoglycemic Japanese subjects. The NAGALA physical examination program was conducted in 1994 at Murakami Memorial Hospital in Gifu City, Japan. For our retrospective study, we selected 15,450 participants who had taken part in this program. Our aim was to explore the potential link between the TyG index, a surrogate marker for insulin resistance, and the presence of prehypertension (pre-HTN) or hypertension (HTN). Our analysis included adjustments for clinical demographic attributes and serum biomarkers. Logistic regression was employed to assess the relationship between the TyG index and the likelihood of pre-HTN or HTN. A total of 15,450 study subjects were included in our analysis. Notably, the prevalence of both pre-HTN and HTN displayed an ascending trend with increasing quartiles of the TyG index. In our comprehensive multivariable logistic regression analysis, when evaluating TyG as a continuous variable, the adjusted odds ratio (OR) for pre-HTN was OR 1.31 [95% CI 1.11-1.56], while for HTN, it was OR 1.76 [95% CI 1.24-2.5] within the fully adjusted model (model 3). When TyG was stratified into quartiles within model 3, the adjusted ORs for pre-HTN were OR 1.16 [95% CI 1.02-1.31], OR 1.22 [95% CI 1.06-1.41], and OR 1.31 [95% CI 1.08-1.59], respectively, using quartile 1 as the reference. The adjusted ORs for HTN in quartiles 2, 3, and 4 were OR 1.22 [95% CI 0.89-1.66], OR 1.4 [95% CI 1.02-1.91], and OR 1.48 [95% CI 1.02-2.15], respectively, within the same model and analysis, with quartile 1 as the reference. Subgroup analysis indicated that the TyG index exhibited a significant positive correlation with the risk of hypertension or prehypertension, except in the subgroup aged ≥65 years. Our study highlights a robust correlation between the TyG index and the likelihood of pre-HTN or HTN in normoglycemic Japanese subjects. This underscores the potential clinical relevance of the TyG index in refining early hypertension management strategies. Nonetheless, the validation of these findings necessitates larger studies with extended follow-up periods.